2023
DOI: 10.1101/2023.10.27.564362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-content RNA-based imaging assay reveals integrin beta 1 as a cofactor for cell entry of non-enveloped hepatitis E virus

Rebecca Fu,
Zoé Engels,
Jasmin Alara Weihs
et al.

Abstract: Hepatitis E virus (HEV) is a major cause of acute hepatitis and mainly transmitted faecal-orally. HEV particles in faeces are non-enveloped, while those in the blood possess a cell-derived lipid envelope. Despite being a global health concern, there is limited understanding of the steps in the HEV life cycle, particularly cell entry. A previous study proposed integrin alpha 3 (ITGA3) as a potential host factor for nHEV entry, but the β-integrin partner that co-mediates HEV entry has not been described. To addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…Our data also suggests, that neHEV CC infection dependents on lysosomal acidification, a condition required for CTS activity. Treatment with NH 4 Cl, an agent that neutralizes endosomal pH, reduced HEV infectivity, which is in line with a recent study by Fu et al, who found that bafilomycin A, another endosomal acidification inhibitor was able to block neHEV CC infection (44).…”
Section: Discussionsupporting
confidence: 88%
“…Our data also suggests, that neHEV CC infection dependents on lysosomal acidification, a condition required for CTS activity. Treatment with NH 4 Cl, an agent that neutralizes endosomal pH, reduced HEV infectivity, which is in line with a recent study by Fu et al, who found that bafilomycin A, another endosomal acidification inhibitor was able to block neHEV CC infection (44).…”
Section: Discussionsupporting
confidence: 88%